The synthesis of novel macrocycles, Part V. The coumarin crown ethers and cation binding with fluorescence spectra - (:unkn) unknown (GORDON BREACH SCI PUBL LTD, 1999)
The 4-H, 4-methyl and g-phenyl derivatives of benzo-alpha-pyrone of 12-crown-4 and 15-crown-5 were synthesised starting from 4-substituted-6,7-dihydroxy- and 7,8-dihydroxybenzo-alpha-pyrones which reacted with dichloropolyethylene glycols in DMF/water/alkali carbonate. The coumarin-macrocycles were identified by elemental analysis, IR, EI-GC-MS as well as H-1, C-13 NMR spectroscopy. The full experimental and spectral data is reported along with ion binding data studied in acetonitrile using fluorescence spectroscopy. The binding of the fluorogenic coumarin-crowns with Li+, Na+ and K+ were recognized as specific alterations on their fluorescence spectra that strongly originated from the structures. The observed CEQFS depending on the bound cation radii and macrocycle size evidenced the rules of cationic recognition of macrocycles. Some 15-crown-5 derivatives exhibited interesting Li+ and Nat binding selectivities.
Keywords: macrocycles; coumarins; ion binding; fluorescence; DERIVATIVES